EMPOWERING THE FUTURE: THE ROLE OF HIGHER EDUCATION IN DEVELOPING 21ST CENTURY SKILLS - Komalasari, Febyana Putri; Nuhaa Maisarah, Sausan; Prasetia, Dimas (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
This research explores the critical role of Higher Education in developing 21st-century skills in students. As the globally required workforce evolves, Higher Education faces the imperative of equipping graduates with the competencies to tackle intricate problems, collaborate effectively, adapt to rapid changes, and prepare graduates with academic skills and the skills to solve complex problems. This research examines current practices, challenges and opportunities in implementing 21st century skills development in Higher Education settings. Expected results indicate that integrating these skills into the curriculum fosters creativity, critical thinking, communication, collaboration, flexibility, initiative, social skills, productivity, and leadership. Therefore, higher education must adapt and focus its efforts on developing these competencies. Modernizing the curriculum for higher education by incorporating 21st-century skills will be viewed as a critical national policy intervention issue, as many of the graduate programs that are currently offered were created several years ago and require current knowledge and radical teaching techniques